2012
DOI: 10.1515/ijamh.2012.045
|View full text |Cite
|
Sign up to set email alerts
|

Parental beliefs and knowledge about male human papillomavirus vaccination in the US: a survey of a pediatric clinic population

Abstract: The purpose of this study is to examine US parental knowledge of human papillomavirus (HPV) in males, views on vaccination, and correlation to vaccination rates. The survey was conducted of clinic population about parental knowledge and beliefs of male HPV health outcomes and vaccination. There were a total of 102 participants who completed the survey. Perceived parental knowledge about the virus was reported as "a lot" by 11%, "some" by 50%, and "very little/nothing" by 38% of the participants. However, knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The relationship between parent’s knowledge and vaccine acceptance/intentions is mixed and equivocal [7377]. Low knowledge in the present group of parents could be explained by the relatively new recommendation of the HPV vaccine for boys and indicate the need to inform parents about the link between HPV and penile, anal and oral cancers as well as GW.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between parent’s knowledge and vaccine acceptance/intentions is mixed and equivocal [7377]. Low knowledge in the present group of parents could be explained by the relatively new recommendation of the HPV vaccine for boys and indicate the need to inform parents about the link between HPV and penile, anal and oral cancers as well as GW.…”
Section: Discussionmentioning
confidence: 97%
“…16 Studies have identified reasons why parents have not vaccinated their children, including: believing the HPV vaccine is not necessary, having concerns over side effects, lacking or having insufficient knowledge about the vaccine, and lack of recommendations from health care providers. 1719 Therefore, enhancing knowledge in parents—particularly Hispanics/Latinos—about HPV and the vaccine will help increase vaccination rates among young males.…”
mentioning
confidence: 99%
“…The current study collected data from four key stakeholder groups from Appalachian communities to examine their acceptability of HPV vaccine for males and potential barriers to vaccinating males against HPV in their communities. Since knowledge about HPV and HPV vaccine for males tends to be low (Gilbert, Brewer, Reiter, Ng, & Smith, 2011; Griebeler, Feferman, Gupta, & Patel, 2012; Reiter, McRee, Gottlieb, & Brewer, 2010), participants’ preferences for future HPV vaccine education programs for males were examined. Results will be useful in planning future HPV vaccine interventions for males living in Appalachia.…”
Section: Introductionmentioning
confidence: 99%